Financial Crisis and Credit Crunch as a Result of Inefficient Financial Intermediation-with Reference to the Asian Financial Crisis - Chen, Zhaohui; Chan-Lau, Jorge (Washington, D.C. : International Monetary Fund, 1998)
This paper develops a model of private debt financing under inefficient financial intermediation. It suggests a mechanism that can generate the following sequence of events observed in the recent Asian crisis: A period of relatively low capital flow despite a steady improvement in economic fundamentals (capital inflow inertia), followed by a fast buildup of capital inflow, and ended with a large capital outflow and domestic credit crunch. Unlike other models requiring large movements in fundamentals or asset prices to explain a financial crisis, this model can exhibit large credit/capital flow swings with moderate changes in the economic and market environment.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet